A review of upgrading heavy oils with supercritical fluids. Issue 92 (8th October 2015) - Yan, Ting; Xu, Jie; Wang, Litao; Liu, Yindong; Yang, Chun; Fang, Tao
<x xml:space="preserve">Abstract</x> Due to the decrease in light crude oil and the ever-increasing demand for the upgrading of heavy oils, the development of new heavy oil processing technology has been attracting wide attention.